Termitariophily: expanding the concept of termitophily in a physogastric rove beetle (Coleoptera: Staphylinidae). (21st December 2018) - Pisno, Raul M.; Salazar, Karen; Lino‐Neto, José; Serrão, José E.; DeSouza, Og
Abstract : 1. Termitophily in some rove beetles is commonly attributed to the striking termite worker resemblance that is provided by the beetles' hypertrophic ('physogastric') abdomen. However, a termite nest may offer to a termitophile additional benefits, such as a continuously repaired shelter. 2. This could apply to Corotoca melantho (Aleocharinae: Corotocini), a viviparous obligatory termitophile staphylinid beetle species. While conferring morphological congruence to its host worker termites, its physogastry may impair mobility, leading to vulnerability and the need for a secure environment. It seems plausible to hypothesise that physogastry in C. melantho would imply in interactions between this termitophile and its host termites as well as its host termitarium. 3. This study provides evidence to build such a hypothesis by inspecting the morpho‐anatomical reproductive traits of this termitophile. It was found that a gradient of growth stages of embryos and larvae in the oviduct explains physogastry in females while pointing to iteroparity. The asynchronous development of oocytes in females, combined with a full developing sequence of sperm cells indicative of continuous spermatogenesis in males, suggests frequent matings. 4. While improving guest–host similarity, physogastry and flightlessness should confer vulnerability to pregnant females, forcing C. melantho to seek close and sheltered environments. These could facilitate the frequent male–female contacts demanded by iteroparity. It is possible, therefore, that physogastry in C. melantho is not only associated with the termites themselves but also with the physical structure of the termitarium. Thus, C. melantho can be hypothesised to be a termitariophile in addition to being a termitophile. Abstract : Physogastry in termitophiles appears to be associated with interindividual interactions: easing host–guest exchanges while allowing the invader to blend into the termite crowd, thereby escaping non‐termitophagous predators. Physogastry in the rove beetle Corotoca melantho seems, additionally, to be associated with prolonged pregnancy, frequent matings, and other reproductive traits that lead to low mobility, vulnerability, and the need for a sheltered and circumscribed environment Termitophily in this beetle could hence be thought to be associated not only with the termites themselves but also with the physical structure of the termite nest.